2018
DOI: 10.1017/s1751731117003676
|View full text |Cite
|
Sign up to set email alerts
|

Anti-inflammatory effects of conjugated linoleic acid isomers and essential fatty acids in bovine mammary epithelial cells

Abstract: Fatty acids are important modulators of inflammatory responses, in particular, n-3 and n-6 essential fatty acids and CLA have received particular attention for their ability to modulate inflammation. The objectives of this study were to compare the effects of CLA and essential fatty acids on the expression of pro and anti- inflammatory cytokines and their protective efficacy against inflammatory status in mammary gland by an in vitro model based on bovine mammary epithelial cells (BME-UV1). Bovine mammary epit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
34
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(38 citation statements)
references
References 32 publications
3
34
1
Order By: Relevance
“…In addition, other studies have clearly marked CLA as a proinflammatory inductor [56,57], indicating that this effect could be greatly heterogeneous depending on physiological conditions, animal species and the dose of CLA. In addition, initial studies in cells showed that CLA, specifically t10,c12, presented ameliorating effects over the production of reactive oxygen species (ROS), correlating to lower gene expression of inflammatory markers [58]. Some studies in humans revealed consistent improvements in inflammation with a reduction in TNF-α (tumour necrosis factor α) and IL-1β (interleukin 1-β) levels [59], while others found increases in TNF-α values [56].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, other studies have clearly marked CLA as a proinflammatory inductor [56,57], indicating that this effect could be greatly heterogeneous depending on physiological conditions, animal species and the dose of CLA. In addition, initial studies in cells showed that CLA, specifically t10,c12, presented ameliorating effects over the production of reactive oxygen species (ROS), correlating to lower gene expression of inflammatory markers [58]. Some studies in humans revealed consistent improvements in inflammation with a reduction in TNF-α (tumour necrosis factor α) and IL-1β (interleukin 1-β) levels [59], while others found increases in TNF-α values [56].…”
Section: Discussionmentioning
confidence: 99%
“…in the present study, cells in the hypoxia group showed increased excretion of conjugated linoleic acid; this is a polyunsaturated fatty acid that has been reported to stimulate the angiogenesis of placental trophoblast cells in the first trimester (56). In addition, conjugated linoleic acid suppresses roS production via the upregulation of peroxisome proliferator-activated receptor γ expression (57,58).…”
Section: Discussionmentioning
confidence: 49%
“…Culture medium and supplements were purchased from Sigma-Aldrich (Milano, Italy). For this study, BME-UV1 cells at passage number between 39 and 41 were used (Dipasquale et al, 2018). The dissociation of the cell monolayer and subcultures was carried out every 2 or 3 days.…”
Section: Cell Culturementioning
confidence: 99%
“…Reactive oxygen species were also determined in cells. The concentration 50 μM of H 2 O 2 and 20 μM of LPS were selected on a previous preliminary cytotoxicity study and on results from other published studies (Basiricò et al, 2017;Dipasquale et al, 2018;Mastrogiovanni et al, 2018).…”
Section: Experimental Designmentioning
confidence: 99%
See 1 more Smart Citation